MANAGEMENT OF RECURRENT INTRAOCULAR LENS SUBLUXATION AFTER IOL REPOSITION IN APHAKIC PEDIATRIC PATIENT WITH SECONDARY GLAUCOMA AND DEPRIVATIVE AMBLYOPIA: Poster Presentation - Case Report - Resident - INDRIYANI; Primawita O. Amiruddin; Sesy Caesarya; Irawati Irfani; Mayasari Wahyu Kuntorini; Feti Karfiati M (Majalah Oftalmologi Indonesia, 2023)
Introduction : Malposition of the intraocular lens (IOL) can be in the form of decentration, subluxation, dislocation, or luxation. Conservative management and surgery are used to treat IOL subluxation. Case Illustration : A 14-year-old boy came to clinic with chief complaint of diplopia since 1 month ago. There were histories of cataract surgery of both eyes in 2014 and 2015 at a secondary hospital, secondary IOL implantation and membranectomy of right eye in December 2017, and IOL reposition of right eye in February 2022. Ophthalmologist examination revealed BCVA of right eye is 0.5 with S+10.00 C-2.25 x180 and left eye is 1/300. The right eye's intraocular pressure was 23 mmHg and the left eye's was 16 mmHg. Anterior segment examination of the right eye showed aphakia with subluxation of the IOL to the inferotemporal (Figure 1) and PC IOL of the left eye. Patient diagnosed with aphakia ODS with IOL subluxation OD, secondary glaucoma OD, astigmatisma Hypermetropia composite OD, astigmatism Myopia Compositus OS, Hypermetropia OD, Myopia Gravior OS, Deprivative Amblyopia ODS, and Last Eye OD. Patient given monofocal spectacles, prednisolone asetat eye drop tapering dose, and timolol maleate eye drop, with observation of IOL position Discussion : Recurrent IOL subluxation without clear signs of zonular or capsular instability in this patient was managed with conservative management using spectacles and medication due to secondary glaucoma. Long-term observation needed to evaluate possibility of repositioning or explanting the IOL in the future. Conclusion : Management of IOL subluxation could temporarily undergo conservative treatment. A surgical approach is considered in cases of recurrent dislocation